Answer:
and ![y = 4](https://tex.z-dn.net/?f=y%20%3D%204)
Step-by-step explanation:
Given
[Correct Question]
![x^2 - 2y = 1](https://tex.z-dn.net/?f=x%5E2%20-%202y%20%3D%201)
![x^2 + 5y = 29](https://tex.z-dn.net/?f=x%5E2%20%2B%205y%20%3D%2029)
Required
Solve using elimination
First, we eliminate x.
Subtract equation (1) from (2)
![x^2 - x^2 + 5y - (-2y) = 29 - 1\\](https://tex.z-dn.net/?f=x%5E2%20-%20x%5E2%20%2B%205y%20-%20%28-2y%29%20%3D%2029%20-%201%5C%5C)
![5y - (-2y) = 28](https://tex.z-dn.net/?f=5y%20-%20%28-2y%29%20%3D%2028)
![5y +2y = 28](https://tex.z-dn.net/?f=5y%20%2B2y%20%3D%2028)
![7y = 28](https://tex.z-dn.net/?f=7y%20%3D%2028)
Divide through ny 7
![y = 4](https://tex.z-dn.net/?f=y%20%3D%204)
Take ![x^2 - 2y = 1](https://tex.z-dn.net/?f=x%5E2%20-%202y%20%3D%201)
Make x^2 the subject
![x^2 = 1 + 2y](https://tex.z-dn.net/?f=x%5E2%20%3D%201%20%2B%202y)
Substitute 4 for y
![x^2 = 1 + 2*4](https://tex.z-dn.net/?f=x%5E2%20%3D%201%20%2B%202%2A4)
![x^2 = 1 + 8](https://tex.z-dn.net/?f=x%5E2%20%3D%201%20%2B%208)
![x^2 = 9](https://tex.z-dn.net/?f=x%5E2%20%3D%209)
Take square roots
![x = \sqrt 9](https://tex.z-dn.net/?f=x%20%3D%20%5Csqrt%209)
![x = 3](https://tex.z-dn.net/?f=x%20%3D%203)
Bear in mind that, when it comes to trigonometric functions, the location of the exponent can be a bit misleading, however recall that sin²(θ) is really [ sin( θ )]²,
![\bf 2sin^2(2x)=2\implies sin^2(2x)=\cfrac{2}{2} \\\\\\ sin^2(2x)=1\implies [sin(2x)]^2=1\implies sin(2x)=\pm\sqrt{1} \\\\\\ sin(2x)=\pm 1\implies sin^{-1}[sin(2x)]=sin^{-1}(\pm 1)](https://tex.z-dn.net/?f=%5Cbf%202sin%5E2%282x%29%3D2%5Cimplies%20sin%5E2%282x%29%3D%5Ccfrac%7B2%7D%7B2%7D%0A%5C%5C%5C%5C%5C%5C%0Asin%5E2%282x%29%3D1%5Cimplies%20%5Bsin%282x%29%5D%5E2%3D1%5Cimplies%20sin%282x%29%3D%5Cpm%5Csqrt%7B1%7D%0A%5C%5C%5C%5C%5C%5C%0Asin%282x%29%3D%5Cpm%201%5Cimplies%20sin%5E%7B-1%7D%5Bsin%282x%29%5D%3Dsin%5E%7B-1%7D%28%5Cpm%201%29)
Step-by-step explanation:
hope i helped pleae mark brainliest
Answer:
okieeeeeee also thanks for the points
Step-by-step explanation:
:)))
Answer:
x is 0
Step-by-step explanation:
subtract the number 3 5 and 8 then combine like terms and 8 on both sides of the equation then simplify after that divide both sides of the equation by the same term then simplify